Peranan Alat Navigasi Radar Dalam Mencegah Resiko Tubrukan Kapal Ketika Berlayar di Bagan Pemisah Atau Alur Pelayaran di Kapal-kapal Milik PT. Pelni Cabang Semarang - Fitri Suprapti; Widar Bayu Wantoro; Rahindra Bayu Kumara (PPPM Polimarin, 2020)
Radio detection and Ranging (radar) as a Navigation equipment for ships above 300 GT has been regulated in the Convention Safety of Life at Sea (SOLAS) chapter V, while in table A-II / 1 of the Standard of Training Certification and Watchkeeping (STCW), regarding the competency standards of seafarers in carrying out duties to watch safe navigation using Radar and ARPA. The most common situation is a meeting of two ships, which to avoid collision according to the Collision Regulation (Colreg). The risk of collision of a ship is the fastest settlement can be determined based on the Distance Closest of Point Approach (DCPA). When the value is less than the desired ship security domain, the right of way is regulated by International Regulation for Preventing Collision at Sea (P2TL). Among the clauses in Colregs rule 9, a ship if sailing in the direction of a narrow channel or waterway must sail as close as possible to the outer boundary of the shipping channel which lies on its starboard side as long as it is safe and can be implemented to avoid the danger of collision of another ship in the narrow channel. The problems in this study lie in the competency of ship officers on the use of radar navigation devices when use in narrow channel and the measures taken to prevent risk of collisions in accordance with the Collision Regulations. The research aims to explain the role of Radar on board ships when navigate in narrow channel safely and to explain the actions that must be taken to prevent collision hazards. Qualitative research that has analytic descriptive characteristics. The population in this study were all deck officers on ships belonging to PT Pelni. It is hoped that this research can produce a solution to reduce the incidence of ship accidents on both national and international shipping